2017
DOI: 10.14423/smj.0000000000000694
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Discharge Disposition of Stroke Patients in Tennessee

Abstract: Objectives Early determination of hospital discharge disposition status at an acute admission is extremely important for stroke management and the eventual outcomes of patients with stroke. We investigated the hospital discharge disposition of patients with stroke residing in Tennessee and developed a predictive tool for clinical adoption. Our investigational aims were to evaluate the association of selected patient characteristics with hospital discharge disposition status and predict such status at the time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 30 publications
1
14
0
Order By: Relevance
“…Another article noted that insurance status was often a determinant of discharge status and ability but did not compare early discharge with current standard and incorporated all stroke patient discharges. 11 One article focused on the economic cost savings of early aneurysm treatment compared with delayed treatment. 12 A study by Alaraj et al 13 investigating reduction of LOS and costs associated with SAH found that LOS has been declining from about 21 days to about 14 days, with similar reduction in costs.…”
Section: National Library Of Medicine Search Engine Resultsmentioning
confidence: 99%
“…Another article noted that insurance status was often a determinant of discharge status and ability but did not compare early discharge with current standard and incorporated all stroke patient discharges. 11 One article focused on the economic cost savings of early aneurysm treatment compared with delayed treatment. 12 A study by Alaraj et al 13 investigating reduction of LOS and costs associated with SAH found that LOS has been declining from about 21 days to about 14 days, with similar reduction in costs.…”
Section: National Library Of Medicine Search Engine Resultsmentioning
confidence: 99%
“…Numerous studies have been conducted on the destination patterns of discharged patients. Cho et al 17 reported that their destinations are associated with several patient characteristics, such as selected demographics, clinical indicators, and insurance status. Thorpe et al 18 conducted a meta‐analysis and found that for each one‐point increase on a functional independence measure, a patient is approximately 1.08 times more likely to be discharged home than to institutionalised care.…”
Section: Discussionmentioning
confidence: 99%
“…Both unadjusted and adjusted ORs with 95% confidence intervals were considered. After that, coefficients (beta) from the multivariate logistic regression model were utilized to derive risk scores [ 5 , 20 , 21 ]. A total risk score was calculated for each patient by taking the sum of corresponding risk scores (see example in Table 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…Early prediction of discharge destination may optimize poststroke care and improve outcomes by mitigating these delays. While many have attempted to predict discharge disposition after stroke [ 1 , 5 7 ], outcomes are limited to validate whether the prediction was truly appropriate for the patient in a clinically meaningful way.…”
Section: Introductionmentioning
confidence: 99%